Prawne warunki wyposażenia ochotniczej straży pożarnej w składniki rzeczowe przez gminę - Błażewski, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego. Wydawnictwo "Szermierz" sp. z o.o., 2023)
The community and the voluntary fire brigade cooperate to ensure fire protection. The forms of cooperation are: a lending communal real estate or movable property, a subsidy and a discount on the purchase of real estate. The volunteer fire brigade should use movable property and real estate to ensure fire protection. The commune has legal means to ensure the correct use of them.
Keywords: community; volunteer fire department; fire protection; public task